2010
DOI: 10.1021/jp909205e
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Mechanism for Nitrate Photochemistry in Snow

Abstract: A reaction mechanism to reproduce photochemical processes in the snow is reported. We developed a box model to represent snow chemistry. Constrained by laboratory experiments carried out with artificial snow, we deduced first a reaction mechanism for N-containing species including 13 reactions. An optimization tool was developed to adjust systematically unknown photolysis rates of nitrate and nitrite (NO(2)(-)) and transfer rates of nitrogen oxides from the snow to the gas phase resulting in an optimum fit wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 64 publications
1
45
0
Order By: Relevance
“…Nitrate ion photochemistry has been proposed to be a major source of OH and NO x in snowpacks. 30,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]137 Sea salt aerosols are also deposited on the snowpack and can become concentrated in a quasi-liquid layer (QLL) on the surface. [138][139][140] Based on the present results, halide ions could significantly impact nitrate photochemistry via enhanced nitrate ion concentrations at the interface of this QLL.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrate ion photochemistry has been proposed to be a major source of OH and NO x in snowpacks. 30,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]137 Sea salt aerosols are also deposited on the snowpack and can become concentrated in a quasi-liquid layer (QLL) on the surface. [138][139][140] Based on the present results, halide ions could significantly impact nitrate photochemistry via enhanced nitrate ion concentrations at the interface of this QLL.…”
Section: Discussionmentioning
confidence: 99%
“…3.3) and this parameter needs thus to be assumed so that simulation results match observations. Interestingly, a recent re-run of a specific nitrate snow-chemistry model where the liquid fraction was reduced by a factor of up to 100 showed that the overall results were surprisingly robust and only slightly sensitive to the assumed volume of the liquid fraction, when other parameters -such as solubility limitswere accounted for and concentrations adjusted (Bock and Jacobi, 2010;Jacobi, 2011).…”
Section: Chemical Processes In Modelsmentioning
confidence: 99%
“…Reactive species are localised in a liquid environment with a constant volume that takes concentration enhancements due to the reduced volume of this liquid fraction into account. A similar approach was used to reproduce laboratory experiments investigating the photolysis of nitrate in snow (Honrath et al, 2000;Dubowski et al, 2002;Jacobi and Hilker, 2007;Bock and Jacobi, 2010;Jacobi, 2011). Over time the applied chemical mechanisms were upgraded from very simplified mechanisms as presented by Liao and Tan (2008) to the most advanced model to date presented by Thomas et al (2011).…”
Section: Conclusion About Chemistrymentioning
confidence: 99%
See 2 more Smart Citations